Workers' compensation claims for traumatic brain injuries among private employers—Ohio, 2001‐2011. Issue 2 (19th November 2019) - Konda, Srinivas; Al‐Tarawneh, Ibraheem S.; Reichard, Audrey A.; Tiesman, Hope M.; Wurzelbacher, Steven J.; Pinkerton, Lynne E.; Meyers, Alysha R.; Hendricks, Scott A.; Tseng, Chih‐Yu; Lampl, Michael P.; Robins, David C.
Abstract: Background: The purpose of this analysis was to identify and prioritize high‐risk industry groups for traumatic brain injury (TBI) prevention efforts. Methods: Workers with TBI from 2001 to 2011 were identified from the Ohio Bureau of Workers' Compensation data. To prioritize industry groups by claim type (lost‐time (≥8 days away from work) and total claims) and injury event categories, we used a prevention index (PI) that averaged TBI counts and rate ranks (PI = (count rank + rate rank)/2). TBI rates per 10 000 estimated full‐time equivalent (FTE = 2000 h/y) workers were calculated. Results: From 2001 to 2011, 12 891 TBIs were identified among private employers, resulting in a rate of 5.1 TBIs per 10 000 FTEs. Of these, 40% ( n  = 5171) were lost‐time TBIs, at a rate of 2.0 per 10 000 FTEs. Spectator Sports had the highest lost‐time TBI rate (13.5 per 10 000 FTEs), whereas General Freight Trucking had the greatest number of lost‐time TBIs ( n  = 293). Based on PIs, General Freight Trucking ranked first for lost‐time TBIs for all injury events combined. Several industry groups within Construction, General and Specialized Freight Trucking, Services to Building and Dwellings, Employment Services, and Restaurants and Other Eating Places ranked high across multiple injury event categories for lost‐time TBIs. Conclusions: The high‐ranking industry groups identified from our study can be used to effectively direct occupational TBI prevention efforts.